Study on the Relativity between Cytogenetics and Cytomorphology and its Prognosis Significance in Children with Acute Myelogenous Leukemia - S Mehta; S Singh; Wang Ning Ling (Journal of Gandaki Medical College, 2018)
Objective: The main objective of this study was to retrospectively evaluate that the cytogenetic abnormalities is an important prognostic factor for the cure of acute myeloid leukemia (AML).